Blood Test Results of Pregnant COVID-19 Patients: An Updated Case-Control Study - Sun, Guoqiang (Front Cell Infect Microbiol, 2020)
Background: Coronavirus disease (COVID-19) is a current global public health emergency. However, current research on the blood test results of pregnant women with COVID-19 is insufficient. Methods: A case-control study was carried out based on clinical blood test results. Pregnant COVID-19 patients, pregnant COVID-19 patients with diabetes, and pregnant COVID-19 patients with hypertension, were assessed in this study. Also, 120 controls were matched by age, parity, fetus number, and presence of chronic disease. T-tests, Chi-square tests, Wilcoxon signed-rank tests, and Kruskal-Wallis tests were used to compare data from the blood tests and liver function indices among the selected groups. Results: Between January 24 and March 14, 2020, 60 pregnant COVID-19 patients delivered at the Maternal and Child Health Hospital of Hubei Province. The average maternal age of pregnant COVID-19 patients was 30.97 years and the mean gestational period was 37.87 weeks. 71.67% (43/60) of pregnant COVID-19 patients gave birth by cesarean delivery. In total, 21.67% (13/60) were diagnosed with diabetes and 18.33% (11/60) were diagnosed with hypertension during pregnancy. Compared to controls, pregnant COVID-19 patients showed significantly lower numbers of blood lymphocytes and higher numbers of neutrophils, as well as higher levels of C-reactive protein and total bilirubin. Among the three groups, pregnant COVID-19 patients with diabetes had significantly higher levels of neutrophils and lower levels of total protein. Aspartate transaminase levels were higher in pregnant COVID-19 patients with hypertension than in pregnant COVID-19 patients with no comorbidities and controls with hypertension. Interpretations: Blood and liver function indices indicate that chronic complications, including hypertension and diabetes, could increase the risk of inflammation and liver injury in pregnant COVID-19 patients.